2024
DOI: 10.1002/imt2.156
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota reshapes cancer immunotherapy efficacy: Mechanisms and therapeutic strategies

Jindong Xie,
Manqing Liu,
Xinpei Deng
et al.

Abstract: Gut microbiota is essential for maintaining local and systemic immune homeostasis in the presence of bacterial challenges. It has been demonstrated that microbiota play contrasting roles in cancer development as well as anticancer immunity. Cancer immunotherapy, a novel anticancer therapy that relies on the stimulation of host immunity, has suffered from a low responding rate and incidence of severe immune‐related adverse events (irAEs). Previous studies have demonstrated that the diversity and composition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…In addition, the microbiota composition or microbiota-derived metabolites are also related to responses to immunotherapy, adverse events, and the heterogeneity of therapeutic effects. The mechanisms underlying gut microbiota-mediated potentiating efficacy while alleviating the side effects of immunotherapy generally differ across bacteria genera and immunotherapy types by enhancing anticancer immunity and modulating the tumor microenvironment [ 30 ]. Nevertheless, there is little research on the exact mechanisms by which the link between the microbiota and gene expression, and consequently the epigenetic pattern, affects the initiation and progression of breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the microbiota composition or microbiota-derived metabolites are also related to responses to immunotherapy, adverse events, and the heterogeneity of therapeutic effects. The mechanisms underlying gut microbiota-mediated potentiating efficacy while alleviating the side effects of immunotherapy generally differ across bacteria genera and immunotherapy types by enhancing anticancer immunity and modulating the tumor microenvironment [ 30 ]. Nevertheless, there is little research on the exact mechanisms by which the link between the microbiota and gene expression, and consequently the epigenetic pattern, affects the initiation and progression of breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that alterations in the gut microbiome composition are associated with the development and progression of colorectal cancer. , Imbalances in microbial diversity, shifts in specific bacterial populations, and changes in the abundance of certain microbial metabolites have been linked to colorectal cancer risk. The identification of these microbiome signatures provides valuable insights into the intricate interplay between the gut microbiome and the host’s immune and metabolic systems, paving the way for the development of microbiome-based biomarkers …”
Section: Molecular Profiling Of Colorectal Cancermentioning
confidence: 99%
“…The human microbiome and its role in health and disease have been at the forefront of scientific research in recent times [1][2][3][4] . To date, bacterial communities from numerous body sites have been screened, both in silico and in vitro, for antimicrobial compounds [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%